Basic or comprehensive strain analyses, which variable is better to predict hard endpoints as clinical heart failure in lymphoma patients receiving anthracyclines. (3rd October 2022) - Quintero-Martinez, J A; Nhola, L F; Alam, M M; Vallejo, B A; Mogollon, R J; Garcia-Arango, M; Cordova-Madera, S N; Herrmann, J; Boddicker, N J; Cerhan, J R; Thompson, C A; Villarraga, H R
Abstract: Background: Speckle tracking echocardiography (STE) has shown to be a good tool to foresee early myocardial dysfunction in lymphoma patients who receive anthracycline based chemotherapy. Conventional STE such as global longitudinal strain (GLS) is a good predictor of cardiotoxicity in these patients, however, a more in-depth characterization of conventional and comprehensive STE parameters to predict a hard end-point as chemotherapeutic related heart failure (HF) has not been evaluated. Purpose: The aim of this prospective study was to evaluate predictability of cancer therapeutic-related clinical HF by conventional and comprehensive STE. Methods: We enrolled 269 Hodgkin & non-Hodgkin lymphoma patients who underwent chemotherapy at Mayo Clinic from 2013 through 2021. All patients had an echocardiogram performed at baseline (T0), during chemotherapy (T1) and after (T2). HF was diagnosed by a cardiologist and defined as the first occurrence after the initiation of chemotherapy. Conventional (GLS) and comprehensive strain analyses that included: global circumferential strain (GCS), global radial strain (GRS), global longitudinal early diastolic strain rate (GLSRe), global longitudinal systolic strain rate (GLSRs), global circumferential early diastolic strain rate (GCSRe), global circumferential systolic strain rate (GCSRs), global radial early diastolic strain rate (GRSRe), and global radial systolic strain rate (GRSRs), were performed offline. Logistic regression analyses were used to evaluate the association of 2D and 3D STE measurements with the development of clinical HF. Results: Overall, 215 (79.9%) patients had non-Hodgkin lymphoma while 54 (20.1%) had Hodgkin lymphoma. Mean age was 58.4±16.1 years and 64.7% of the patients were males. The most prevalent comorbidities were hypertension (101/37.5%), dyslipidemia (87/32.3%) and diabetes (28/10.4%). HF occurred in 21 (7.8%) patients, including 9 (3.3%) during chemotherapy and 12 (4.5%) after chemotherapy. The best predictors of HF were: i) GLSRe and GCSRs performed at baseline (T0) to predict HF at T1 with an AUC of 0.85 each and p values of 0.0006 and 0.0005 respectively (Table 1); ii) GCSRs and GCS at baseline (T0) to predict HF at T1 or T2 with AUCs of 0.82 (p, <0.0001) and 0.81 (p, 0.0004), respectively. Basic strain (GLS) was able to predict HF when measured at T0 but not when measured at T1. All the AUCs for GLS were below 0.75 (Figure 1). Conclusions: To our knowledge this is the first study to evaluate the use of conventional and comprehensive STE to predict a hard end-point as heart failure in patients with lymphoma who received anthracyclines. Comprehensive STE measurements as GLSRs, GLSRe, GCS, GCSRs and GCSRe are better than GLS to predict HF in patients with lymphoma who received anthracycline based chemotherapy. These findings can be crucial for the management of these patients by guiding when to start cardioprotection and/or avoid interruptions of cancer treatment. Funding Acknowledgement: Type of funding sources: Private hospital(s). Main funding source(s): Department of cardiovascular diseases, Mayo Clinic, Rochester, MN